Pengaruh Servant Leadership, Work Ability Terhadap Employee Performance Dengan Menggunakan Self Esteem Sebagai Variabel Intervening Pada Pegawai Pemerintah Kota Surabaya - Kusumaningrum, Sari Dewi; Mujanah, Siti; Fianto, Achmad Yanu Alif (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This researchi aims to examine 4 (four) variables : servant leadership, work ability and self-esteem on employee performance, and self-esteem as an intervening variable between servant leadership, work ability and employee performance.This type of research is quantitative research. This research was conducted at the Karang Pilang District Office, Surabaya City. Sampling used random sampling technique with the Slovin formula.Respondent were 88 respondents rom a population of 112 employees. The data obtained by distributing questionnaires was then analyzed using SEM PLS and hypothesis testing using the SmartPLS 4 tool. The results of this study showed that the direct influence was a positive and significant relationship between work ability,self-esteemind employee performance.The hypothesis wass accepted . Meanwhile, the direct influence of servant leadership on employee performance and self-esteem si rejected.In the indirect influence of servant leadership on employee performance, the hypothesis is rejected,which means that self-esteem cannot ne an intervening variable. Meanwhile, the indirect effect of wor ability on employee performance is that the hypothesis is accepted,self-esteem can be an intervening variable.